A novel strategy for producing compost with enhanced biopesticide properties through solid-state fermentation of biowaste and inoculation with Bacillus thuringiensis. (December 2017) - Ballardo, Cindy; Barrena, Raquel; Artola, Adriana; Sánchez, Antoni
Highlights: Bacillus thuringiensis (Bt) growth on non-sterile OFMSW has been demonstrated. Bt-enriched compost can be produced from non-sterile biowaste. Non-sterile OFMSW can be valorized through semi-continuous SSF and Bt inoculation. The self-sustained inoculation procedure proposed will enhance process economics. Abstract: In the framework of a circular economy, organic solid wastes are considered to be resources useful for obtaining value-added products. Among other potential uses, biodegradable wastes from agricultural, industrial, and domestic sources are being studied to obtain biopesticides through solid-state fermentation (SSF), mainly at the laboratory scale. The suitability of biowaste (source-selected organic fraction of municipal solid waste) for use as a substrate for Bacillus thuringiensis (Bt) growth under non-sterile conditions in a 10 L SSF reactor was determined in this study. An operational strategy for setting up a semi-continuous process yielding a stabilised organic compost-like material enriched with Bt suitable for use as a soil amendment was developed. Concentrations of 1.7·10 7 –2.2·10 7 and 1.3·10 7 –2.1·10 7  CFU g −1 DM for Bt viable cells and spores, respectively, were obtained in the final material. As the results confirmed, Bt-enriched compost-like material with potential biopesticide properties can be produced from non-sterile biowaste.